Comprehensive analysis of arachidonic acid metabolism-related genes in diagnosis and synovial immune in osteoarthritis: based on bulk and single-cell RNA sequencing data - Tu, Bizhi; Fang, Run; Zhu, Zheng; Chen, Guang; Peng, Cheng; Ning, Rende (Inflammation research, 2023)
Background Osteoarthritis (OA) is one of degenerative-related arthritis, which can be aggravated by low-grade synovitis. It is known that arachidonic acid (AA) dysmetabolism brings OA synovitis. However, the impact of synovial AA metabolism pathway (AMP) related genes on OA remains uncovered. Methods Here, we conducted a comprehensive analysis to explore the impact of AA metabolism genes in OA synovium. We obtained transcriptome expression profiles from three raw datasets related to OA synovium (GSE12021, GSE29746, GSE55235) and identified the hub genes of AA metabolism pathways (AMP) in OA synovium. An OA occurrence diagnostic model was constructed and validated based on the identified hub genes. Then, we explored the correlation between hub gene expression and the immune-related module using CIBERSORT and MCP-counter analysis. The unsupervised consensus clustering analysis and weighted correlation network analysis (WGCNA) were utilized to identify robust clusters of identified genes in each cohort. Moreover, the interaction between the hub genes of AMP and immune cells was elucidated through single-cell RNA (scRNA) analysis by scRNA sequencing data from GSE152815. Results We found that the expression of AMP-related genes was up-regulated in OA synovium, and seven hub genes (LTC4S, PTGS2, PTGS1, MAPKAPK2, CBR1, PTGDS, and CYP2U1) were identified. The diagnostic model that combined the identified hub genes showed great clinical validity in diagnosing OA (AUC = 0.979). Moreover, significant associations were noticed between the hub genes' expression, immune cell infiltration, and inflammatory cytokine levels. The 30 OA patients were randomized and clustered into three groups using WGCNA analysis based on the hub genes, and diverse immune status was found in different clusters. Of interest, older patients were more likely to be classified into a cluster with higher levels of inflammatory cytokines IL-6 and less infiltration of immune cells. Based on the scRNA-sequencing data, we found that the hub genes had relatively higher expression in macrophages and B cells than other immune cells. Moreover, inflammation-related pathways were significantly enriched in macrophages. Conclusion These results suggest that AMP-related genes are closely involved in alterations of OA synovial inflammation. The transcriptional level of hub genes could serve as a potential diagnostic marker for OA.